Exploration and practice of zero-carbon intra-park in the context of Carbon peaking and Carbon neutrality Goals： A case study on an intra-park - Zhang Jun; Qin Yipeng; Feng Chao; Qiao Biao; Song Jialiang; Liang Shukui; Mu Lichun; Wang Lu (E3S Web of Conferences, 2023)
Aiming at the planning of zero carbon park under the background of double carbon, tins paper takes an industrial park as an example, and analyzes and evaluates the industrial planning situation, energy resources situation and energy plaiming situation of the park based on the concept of “passive priority, active optimization”. Taking the project as the blueprint, integrating the building energy-saving measures and the advanced nature and carbon reduction ability of the integrated smart energy technology, starting from the overall optimization layout of the park, covering the industrial structure, buildings, transportation, energy and other key areas of the park, the comprehensive application of low-carbon technology forms such as building micro-environment, ultra-low energy consumption building system, efficient integrated energy system and renewable energy. Total carbon emissions as the core goal, to achieve the goal zero carbon zone. This study for the project and project time zero carbon building and future zero carbon park planning to provide the reference of the same kind of park.